Phosphinoyl Radical Initiated Vicinal Cyanophosphinoylation of Alkenes - Zhang, Pei-Zhi; Zhang, Ling; Li, Jian-An; Shoberu, Adedamola; Zou, Jian-Ping; Zhang, Wei (Organic letters, 2017)
A double-functionalization reaction of alkenes through Mn(OAc)3-mediated phosphinoyl radical addition followed by CuCN-catalyzed cyanation is introduced. This one-pot reaction is performed under mild conditions to afford vicinal cyanophosphinoylation products.